Targeted genome fragmentation with CRISPR/Cas9 enables fast and efficient enrichment of small genomic regions and ultra-accurate sequencing with low DNA input (CRISPR-DS) - Nachmanson, Daniela; Lian, Shenyi; Schmidt, Elizabeth K.; Hipp, Michael J.; Baker, Kathryn T.; Zhang, Yuezheng; Tretiakova, Maria; Loubet-Senear, Kaitlyn; Kohrn, Brendan F.; Salk, Jesse J.; Kennedy, Scott R.; Risques, Rosa Ana (Genome Research, 2018)
Next-generation sequencing methods suffer from low recovery, uneven coverage, and false mutations. DNA fragmentation by sonication is a major contributor to these problems because it produces randomly sized fragments, PCR amplification bias, and end artifacts. In addition, oligonucleotide-based hybridization capture, a common target enrichment method, has limited efficiency for small genomic regions, contributing to low recovery. This becomes a critical problem in clinical applications, which value cost-effective approaches focused on the sequencing of small gene panels. To address these issues, we developed a targeted genome fragmentation approach based on CRISPR/Cas9 digestion that produces DNA fragments of similar length. These fragments can be enriched by a simple size selection, resulting in targeted enrichment of up to approximately 49,000-fold. Additionally, homogenous length fragments significantly reduce PCR amplification bias and maximize read usability. We combined this novel target enrichment approach with Duplex Sequencing, which uses double-strand molecular tagging to correct for sequencing errors. The approach, termed CRISPR-DS, enables efficient target enrichment of small genomic regions, even coverage, ultra-accurate sequencing, and reduced DNA input. As proof of principle, we applied CRISPR-DS to the sequencing of the exonic regions of TP53 and performed side-by-side comparisons with standard Duplex Sequencing. CRISPR-DS detected previously reported pathogenic TP53 mutations present as low as 0.1% in peritoneal fluid of women with ovarian cancer, while using 10- to 100-fold less DNA than standard Duplex Sequencing. Whether used as standalone enrichment or coupled with high-accuracy sequencing methods, CRISPR-based fragmentation offers a simple solution for fast and efficient small target enrichment.